2019
DOI: 10.3164/jcbn.19-47
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic gastric mucosal atrophy as a predictor of colorectal polyps: a large scale case-control study

Abstract: Although some studies have indicated a correlation betweenHelicobacter pylori infection and the risk of colorectal neoplasms, these findings have not been consistent and are controversial. This case control study aimed to investigate the association between endoscopic gastric mucosal atrophy and colorectal polyp occurrence. Records of 7,394 participants who underwent colonoscopy examinations from August 2008 to July 2018 were reviewed retrospectively. A total of 2,404 subjects were registered; 1,565 (65.1%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…We speculated that the contradictory results might be partly related to different H.pylori detection methods, regions and races, and small sample sizes. As for the relationship between AG and CPs, several studies have shown an association between them 13 , 18 . Recently, Sonnenberg et al 19 conducted a large retrospective study to assess the connection between colonic polyps and abnormal gastric histopathology, based on 302 061 patients from a national database.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the contradictory results might be partly related to different H.pylori detection methods, regions and races, and small sample sizes. As for the relationship between AG and CPs, several studies have shown an association between them 13 , 18 . Recently, Sonnenberg et al 19 conducted a large retrospective study to assess the connection between colonic polyps and abnormal gastric histopathology, based on 302 061 patients from a national database.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also demonstrated that atrophic gastritis with Hp infection is a risk factor for colorectal polyps [ 23 ]. However, in the current study, Hp infection was not an independent risk factor for colorectal polyps.…”
Section: Discussionmentioning
confidence: 99%
“…There have been increasing documents showing that the prevalence of colorectal ailments has been linked to the infection with H. pylori, whereas no consistent conclusion has been drawn by far [24][25][26][27] . Boyuk B et al investigated 341 subjects and showed that the progression of colorectal adenoma and carcinoma is independent of H. pylori infection [24] .…”
Section: Discussionmentioning
confidence: 99%